Research on the Design and Application of Narrative Illustration on Food Packaging - Pi, Qing; Pan, Jing; Guo, Zidi; Guo, Miao (Transactions on Social Science, Education and Humanities Research, 2023)
Packaging design plays an important role in the promotion process of commodities, and commercial illustration is a form of expression using commercial purpose. With the development of personalized packaging design, the advantages of illustration such as adaptability and diversity are fully displayed in packaging design, and are increasingly widely used. Improve the artistic and practical value of food packaging. However, with the rapid development of society, people’s pace of life continues to accelerate, people are increasingly strong psychological demands. Economic conditions are becoming more and more superior, art education, aesthetic training, as well as the impact of the Internet aesthetic vision, the requirements of food packaging is also increasingly high, narrative illustration picture effect is rich, the expression of the story of the content of the story, the story can be very good to convey the characteristics of the food as well as the brand culture, and at the same time, to meet the pursuit of people’s personalized packaging, narrative illustration is also the medium of emotional communication between the commodity and the consumer is the key of brand The key to cultural interpretation, the interactive experience between consumers and food brands. In this paper, we try to analyze the demand of consumers for narrative illustration in food packaging, and discuss the expression of narrative illustration art on food packaging, aiming at realizing the full conveyance of product information, and at the same time, making the whole commodity rich in unique creativity and ideological connotation.